Epidemiology of Vestibular Impairments in a Pediatric Population - Wiener-Vacher, Sylvette R.; Quarez, Juliette; Priol, Audrey Le (Seminars in Hearing, 2018)
The purpose of this study was to report the prevalence of vestibular impairment (VI) in children (n = 2,528) referred for complete vestibular testing because of balance disorders (BD) or hearing loss (H). A VI was shown in 51.5% of the children tested (1,304/2,528). For BD (e.g., vertigo, dizziness, instability, delay in posturomotor development), VI was found in 36.5% (n = 379/1,037). The most frequent causes of BD with VI included inner ear malformation (13.5%), delay in posturomotor development (13.4%), hearing loss revealed with vertigo (3.9%), trauma (3.9%), vestibular neuritis (3.3%), meningitis (2.5%), Meniere-like syndrome (1.1%), BPPV posttrauma (1%), labyrinthitis (0.4%), and unknown etiology (19.6%). Normal responses to the complete battery of tests (n = 658, 63.5%) excluded a vestibular origin to BD, leading to other diagnoses: principally migraine (15.6%), ophthalmological disorders (15.1%), neurological disorders (including delay in posturomotor development; 14.4%), orthostatic hypotension, or somatoform dizziness (<1%). Of the children referred for hearing loss (n = 1,491), 68.5% were tested without cochlear implantation (CI; n = 1,022). In this group, 54.5% presented with VI (n = 557). This was mostly found in cytomegalovirus infection, inner ear malformation, and genetic syndromes. Profound hearing loss candidates for cochlear implants had complete bilateral vestibular loss in 20% and delay in posturomotor development, and 80% had partial or normal vestibular function and normal posturomotor development. VI was found after CI in 50% on the side of the implant (partial in 41% and complete in 9%). VI is present in 36.5% of children referred to our center for BDs and 54.5% for hearing loss. Vestibular testing permits ruling out peripheral VI and hence seeking other causes for BDs such as migraine and ophthalmological disorders and also helps lower the risk of inducing bilateral complete vestibular loss in CI protocols.
Keywords: balance disorders; vertigo; dizziness; hearing loss; etiologies; pediatric